ANALISIS PENGGUNAAN VIDEO KONTEN TUTORIAL TEKNIK PUKULAN SERVICE BACKHAND BULUTANGKIS PADA PEMBELAJARAN PJOK KELAS X SMA NEGERI 1 ANJATAN - Mohammad Fajar Nugrahai; Irfan Zinat Achmad; Akhmad Dimyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract: Researchers observe inadequate explanations and demonstrations byPJOK teachers, leading to student boredom, low motivation, and difficultyunderstanding material. During PJOK lessons, students fail to grasp themovements and techniques they should learn and practice. The research aims toexamine video tutorial use, student responses, and outcomes in learning theBackhand Service technique in badminton. This research method employsqualitative techniques with a descriptive approach, producing descriptive data inthe form of written or spoken words from individuals or observable behaviors. Theuse of tutorial videos for backhand service techniques in badminton among tenth-grade students at SMA Negeri 1 Anjatan is found to be effective and easilyapplicable, enhancing the learning process in PJOK education. The application oftutorial video content for backhand service techniques in physical educationsignificantly enhances learning, enabling students to effectively explain thematerial, including definitions, execution methods, and rules of the backhandservice technique in badminton, and allowing them to practice the techniqueproficiently.